Changes in the Linear Relationship between Muscle Contraction Intensity and Muscle Hardness after Rectus Femoris Muscle Strain. (25th November 2019) - Inami, Takayuki; Shimizu, Takuya; Osuga, Tomoaki; Narita, Takaya; Hirose, Norikazu; Murayama, Mitsuyoshi
Abstract : Objective . Joint torque differences between healthy and rehabilitated legs are often measured as a clinical index of recovery from muscle strain injury. Unfortunately, it should be noted that this is a questionable evaluation measure of the muscle after injury because it is a composite value including related cooperating muscles. Meanwhile, the use of ultrasound elastography for the measurement of individual muscle mechanical properties (i.e., muscle hardness) has recently expanded. The purpose of this study was to examine, using ultrasound elastography, the differences in the linear relationship between muscle contraction intensity and muscle hardness during knee extension in athletes who had recovered from grade II rectus femoris muscle strain injury through comparison of the healthy and rehabilitated legs. Methods . Six athletes participated. Rectus femoris muscle hardness, determined during isometric contraction at 10%, 20%, 30%, and 40% of maximum voluntary contraction, was evaluated using ultrasound strain elastography. Results and Conclusion . The results indicated that for the healthy legs, the strain ratios, as indicated by muscle hardness, decreased linearly (became harder) with contraction intensity, but the strain ratios for the rehabilitated legs decreased nonlinearly. These results show the danger of judging the recovery period using only the difference between healthy and rehabilitated muscle strengths and the importance of evaluating individual muscles.